2011
DOI: 10.3945/jn.111.143602
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phospholipids Ameliorate Fructose-Induced Hepatic Lipid and Metabolic Abnormalities in Rats

Abstract: Overconsumption of fructose results in hepatic dyslipidemia, which has a documented correlation with metabolic syndrome. We examined whether the ingestion of phospholipids (PL) from soybeans prevents fructose-induced metabolic abnormalities. Rats were fed either a fructose-free diet (C), a 60% fructose diet (F), or a 60% fructose plus 3% PL diet (F-PL) for 10 wk. At wk 8, plasma glucose concentrations after glucose loading were significantly higher in rats fed the F diet than in rats fed the C and F-PL diets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Fructose administration activates ChREBP which acts in synergy with SREBP to increase the expression of lipogenic genes [12, 2628]. Incubation of HepG2 cells with fructose also induces upregulation of nuclear ChREBP and SREBP1c protein expression [29]. In contrast, SREBP1c is stimulated by insulin [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fructose administration activates ChREBP which acts in synergy with SREBP to increase the expression of lipogenic genes [12, 2628]. Incubation of HepG2 cells with fructose also induces upregulation of nuclear ChREBP and SREBP1c protein expression [29]. In contrast, SREBP1c is stimulated by insulin [14].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between fructose feeding and hepatic expression of PPAR- α and its responsive genes is still controversial. Some studies have reported that fructose feeding downregulated hepatic expression of PPAR- α , CPT1a, and/or ACO genes [1820, 38], whereas others found no change in the expression of these genes [28, 29, 3941]. It has been demonstrated that activation of PPAR- α by its agonist fenofibrate strongly induced the expression of hepatic lipogenic genes FAS, ACC1, and SCD1, accompanied by induction of hepatic CPT1a, ACO, and CD36 in mice [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fructose ingestion at high doses increases expression of the genes encoding for lipogenic enzymes via the activation of SREBP1 in the liver (29). Thus we have analyzed the expression of SREBP1c, SREBP2, and their chaperone protein SCAP in the liver of FRT-and GLC-drinking mice.…”
Section: Discussionmentioning
confidence: 99%
“…Further, although many animal models have used excessively high levels of fructose (30-60% of total energy intake in some cases) not reflective of average human intake, 47,93 these studies have reinforced the adverse effects of excessive fructose consumption. [94][95][96] More recently, animal studies have turned their attention to diets with human intake-relevant fructose loadings (~10% w/v), 81,97-101 predominantly in the rat and mouse. These studies continue to demonstrate fructose-specific metabolic abnormalities, including altered hepatic insulin sensitivity and lipid metabolism.…”
Section: Fructose and Adult Health Impacts: The Debate Continuesmentioning
confidence: 99%